Analysis of Mechanical Properties of Air-Ribbed Skeleton Membrane Structure - Lei Zheng; Jiannan Xu; Feng Li; Jun Zhang; Ronghua Su; Jing Wang; Ying Liu; Yi Ru (Applied Sciences, 2023)
The existing large inflatable membrane structure is complex in structure and takes a long time to be extended. In this paper, an air-ribbed skeleton membrane structure is proposed to meet the requirement of camp and emergency tents needing to be set up quickly and easily. Ten single-arch air ribs are arranged side by side to support the tarpaulin, and wind ropes are added to the end and side faces of the tarpaulin to remain stable. The finite element model of the air-ribbed skeleton membrane structure is established to analyze the stress and the displacement of the membrane structure under combined wind and snow loads. The maximum displacement (439.4 mm) and maximum stress (29.94 MPa) are both within the safe standard. The stress and the displacement of the membrane structure in the wind load case is affected by the angle of the wind. The value of maximum stress and displacement at the wind angle of 90° are both lower than those at 0° and 45° in the wind load case. It is advisable to align the site layout of the membrane structure at the wind angle of 90°. The effect of the angle of wind ropes on the stress and displacement of the membrane structure is also studied. The maximum stress and displacement in the case when the angle of wind rope is 30° is smaller than those in the case when the angle of wind ropes is 45°. It is recommended that the wind rope should be laid at 30° to reinforce the membrane structure.